Dairy production of Jersey cattle estimation using temporary, intrinsic and environmental variables (UNED Research Journal, 2020)
Introduction: Production systems looking for efficient use of resources are continually predicting the dairy production behavior of production animals. Objective: To generate a mathematical prediction model of dairy production that associates climate conditions at the moment the information was collected with the intrinsic characteristics of the livestock in two production systems located at 600 and 1 800m.a.s.l. in Cartago, Costa Rica. Methods: We used a database created from 2003 to 2014 for the production system located at 600m.a.s.l. with a total of 61 animals, while for the system established at 1 800m.a.s.l. the information was recorded between the 2011 to 2014, with 387 animals. Results: We generated three equations under the hypothesis that the producers do not gather and record the complete information. The first one considers the interaction of environmental, temporal, and intrinsic variables of the animal, while the other two equations separate the environmental effect and the characteristics of the animal. We determined that at 600m.a.s.l. the temperature (-4,52), lactation number (-0,99), the relative humidity (-0,16), the moth (-0,14) and lactation days (-0,02) have an adverse effect on milk production, while precipitation (0,0004), radiation (0,044), the age of the animal (0,084) and humidity and temperature index (2,68) favor productivity. At the same time, at 1 800m.a.s.l. radiation (-0,06), relative humidity (-0,04) and lactating days (-0,03) decreased animal productivity, on the other hand, the assessment precipitation (0,02), month (0,07) and lactation number (0,57) increased. Conclusion: These equations are input so that those responsible for the production systems have a way to select animals or take actions to maintain animal homeostasis.
Keywords: relative humidity; temperature; dairy cattle; Bos taurus; heat stress